Experimental investigation of transonic external fan cowl separation - Sabnis, Kshitij; Boscagli, Luca; Babinsky, Holger; MacManus, David G.; Sheaf, Christopher T. (Association Aeronautique et Astronautique de France (3AF), 2023)
When a civil aircraft engine is shut down during the cruise phase of flight and thus begins to windmill, a supersonic region forms on the external surface of the fan cowl. The terminating normal shock can separate the turbulent boundary layer developing on this external surface. A series of experiments are performed in a quasitwo-dimensional wind tunnel rig to investigate the influence of various parameters on this flow problem. As the engine mass-flow rate is reduced, an increase in normal shock strength results in the onset of flow separation which thickens the boundary layer developing on the external fan cowl surface by a factor of three. A reduction in incoming Mach number from the nominal value of 0.65 to 0.60 weakens the shock wave and thus delays flow separation. If the incoming boundary layer is laminar rather than turbulent, the normal shock Mach number is observed to increased by 10%. Despite the stronger shock, no significant flow separation can be detected even for the lowest engine mass-flow rates studied and the external nacelle surface boundary layer is measured to be thinner than for the turbulent case.